A new soft computing model for daily streamflow forecasting - Sammen S.S.; Ehteram M.; Abba S.I.; Abdulkadir R.A.; Ahmed A.N.; El-Shafie A. (Springer Science and Business Media Deutschland GmbH, 2023)
Climate change; Data streams; Floods; Forecasting; Genetic algorithms; Hydroelectric power plants; Mean square error; Multilayer neural networks; Particle swarm optimization (PSO); Soft computing; Soil conservation; Water conservation; Water management; Water supply; Flow quantification; Multi layer perceptron; Optimization algorithms; Predicting models; Root mean square errors; Soft computing models; Streamflow forecasting; Watershed management; Stream flow; algorithm; forecasting method; hydroelectric power plant; numerical model; optimization; principal component analysis; streamflow; watershed; Helianthus